Green Taxonomy as a Basic Concept of Sustainable Finance Through Green Bond Issuance - Prakoso, Bhim; Hariyani, Iswi; Wahjuni, Edi; Ali, Moh.; Wardhana, Rhama Wisnu (Acten Journal Law Review, 2025)
The increasing awareness of global issues in the sustainable development goals (SDGs) agenda initiated by the UN, has given rise to green investment in the economic sector, especially in the financial aspect. Referring to capital activities aimed at projects that address global issues. In recent years, green investment practices have begun to increase both in terms of the number of debt securities from individuals and countries participating in supporting the realization of SDGs 2030. In the Indonesian Capital Market there is a new financial instrument called green bonds. Green Bonds are regulated through the Financial Services Authority Regulation (POJK) Number 60 of 2017, as is the authority held by OJK regarding the regulation of the financial services sector in Indonesia. This article will discuss the legal status of green bonds in Indonesia and whether green bonds can be one of the financing schemes in Indonesia. However, interest in green bonds is still quite low considering the obstacles that result in investment risks. The research method with a normative juridical type, using literature and descriptive studies in solving problems, this research is expected to not only answer the risks but also the utility of green bonds in realizing economic and environmentally sustainable development goals.